From Magnetic to Nonlinear Optical Switches in Spin‐Crossover Complexes. Issue 5 (10th January 2013) - Lacroix, Pascal G.; Malfant, Isabelle; Real, Jose‐Antonio; Rodriguez, Vincent
Abstract: Various attempts to combine magnetic and nonlinear optical (NLO) properties in a molecule are reviewed, with a special focus on the possibility of interplay between the magnetic component and the quadratic ([prop] E 2 ) NLO response. This multidisciplinary research leads to the idea of spin‐crossover‐induced (SCO‐induced) NLO switching and is evaluated at the synthetic level, with insights provided by computational chemistry. The need for nontraditional experimental setups to record NLO properties in the solid state is discussed. Abstract : Among various investigations of the quadratic ( β ) nonlinear optical (NLO) properties of molecular materials with different magnetic properties, a correlation is found between the spin crossover phenomenon and the NLO response of an iron(II) complex, leading to a new possibility for magnetically induced NLO switching.